An exploration of context and learning in endurance sports coaching - Kirkland, Andrew; Cowley, Joe (Frontiers in Sports and Active Living, 2023)
Introduction This study explored contextual factors which influence coach learning of an international cohort of endurance sports coaches. Methods Following ethical approval, 839 coaches, 612 coached athletes and 8,352 non-coached athletes participated in the research. A critical realist research philosophy was adopted, in which self-completion surveys were developed in consultation with coaches and industry end-users. Results and Discussion The context was dominated by remote coaching practices and digital technology which shaped how coaches learn and thus, what it meant to be a coach. Unmediated learning sources were biophysically biased and largely delivered through marketised platforms designed to sell products. The study findings have broader implications within sport and education, in which it is suggested that remote coaching and learning platforms may sometimes create a sense of psycho-emotional detachment in which capacity for learning can be limited.